2019
DOI: 10.2174/1874331501913010133
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Nitrogen and Phosphorus Uptake of Sorghum Plants as Affected by Green Manuring with Pea or Faba Bean Shell Pod Wastes Using 15N

Abstract: Background: During the freezing or canning preparation process of green grain leguminous, large amounts of shell pods are considered as agricultural organic wastes, which may be used as Green Manure (GM) for plant growth enhancement. Objective: Evaluation of the effectiveness of soil amended with shell pod wastes of pea (PGM) or faba bean (FGM) as GM on growth, nitrogen and phosphorus uptake in sorghum plants. Methods: Determination of the impact of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…One plausible explanation for the reduced weed growth found in CC pots may be related to the C/N ratio and the lower nutrient content of this raw waste compared to CG and F (Table S1). The C/N ratios for CG and F are around 23:1 and 18:1, respectively [33,37]. However, CC has a C/N ratio of 120:1 [50], which is very high, explaining its poor quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One plausible explanation for the reduced weed growth found in CC pots may be related to the C/N ratio and the lower nutrient content of this raw waste compared to CG and F (Table S1). The C/N ratios for CG and F are around 23:1 and 18:1, respectively [33,37]. However, CC has a C/N ratio of 120:1 [50], which is very high, explaining its poor quality.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chrysargyris et al [54] found that a substrate mixture including CG showed enriched content of N, P, K, and some micronutrients. In the case of F waste, Al-Chammaa et al [37] proved that adding green manures of V. faba pods as soil amendment with, 15 days before plant sowing, provided a considerable amount of N requirements for Sorghum plants. These three studies were conducted in pots using a range of substrates (peat-perlite and field soil).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The richest habitat for biodiversity on earth is the soil, which is rich in organic and inorganic material that provides habitat for various biological communities 16 , 17 . Soil microorganisms are involved in ecological processes such as nutrient decomposition and supply, and they are an essential component of growth and yield formation 18 .…”
Section: Introductionmentioning
confidence: 99%